VIOLÊNCIA E A DESTRUTIVIDADE DA SOCIEDADE DO CAPITAL: consequências para as políticas públicas - Raquel de Matos Lopes Gentilli (Universidade Federal do Maranhão, 2014)
This paper, a theoretical and analytical essay aims to reflect about the globalization of capital and its neoliberal deregulation which come fraying sociability, whose phenomenal processuality can be observed in current forms of violence. The reflection is realized structural and methodological perspective of totality, considering the relations of class power and that materialize in the state and its policies. Discuss the implications of the phenomenon of uncontrollable expansion of capital in the current social relations, and how the state is unable to respond effectively to public policies. Concludes that individuals, sectors, classes and more vulnerable nations are at the mercy of international structural interests of contemporary power, where violence draws only one of the current civilizational traits desirable logical and fair.